Bibliometric Analysis on Women’s Leadership Aspiration (2001:2021) - K. H, Ms. Asha Lakshmy; Kumar, Dr. S.A. Senthil (The journal of contemporary issues in business and government, 2023)
The persistent underrepresentation of women in leadership positions is a widely acknowledged concern. This study employs bibliometric analysis to critically examine the existing corpus of literature on women’s aspirations for career advancement and their drive towards leadership roles, sourced from the comprehensive Scopus database. A systematic review of the literature was conducted using the PRISMA standards. Data from 2001-2021 sourced from the Scopus database was used in the study. A total of 45 publications were identified and evaluated based on their titles, abstracts and keywords resulting in a final sample of 42 articles that underwent data mining and qualitative analysis through the use of Biblioshiny and VOS viewer tools. The findings highlight the most influential literature in the field, the publishing trends, and further areas for research that will help build a conceptual framework for future behavioural research. Recognizing the factors that impact women’s career advancement and creating a supportive environment is crucial to promoting gender equality. The outcomes of this study have both theoretical and practical implications and align with the objective of achieving gender equality under the 2030 Sustainable Development Goals agenda. The study provides a foundation for the attainment of this goal by shedding light on the issue.